A membrane penetrating peptide aptamer inhibits STAT3 function and suppresses the growth of STAT3 addicted tumor cells - Borghouts, Corina (Landes Bioscience, 2012)
Cancer cells are characterized by the aberrant activation of signaling pathways governing proliferation, survival, angiogenesis, migration and immune evasion. These processes are partially regulated by the transcription factor STAT3. This factor is inappropriately activated in diverse tumor types. Since tumor cells can become dependent on its persistent activation, STAT3 is a favorable drug target. Here, we describe the functional characterization of the recombinant STAT3 inhibitor, rS3-PA. This inhibitor is based on a 20 amino acid peptide which specifically interacts with the dimerization domain of STAT3. It is integrated into a thioredoxin scaffold and fused to a protein transduction domain. Protein gel blot and immunofluorescence analyses showed that rS3-PA is efficiently taken up by cells via an endocytosis independent mechanism. Intracellularly, it reduces the phosphorylation of STAT3 and enhances its degradation. This leads to the downregulation of STAT3 target gene expression on the mRNA and protein levels. Subsequently, tumor cell proliferation, survival and migration and the induction of angiogenesis are inhibited. In contrast, normal cells remain unaffected. Systemic administration of rS3-PA at doses of 7.5 mg/kg reduced P-STAT3 levels and significantly inhibited tumor growth up to 35% in a glioblastoma xenograft mouse model.